2021
DOI: 10.1016/j.esmoop.2021.100258
|View full text |Cite
|
Sign up to set email alerts
|

Priorities and preferences of advanced soft tissue sarcoma patients starting palliative chemotherapy: baseline results from the HOLISTIC study

Abstract: Available online xxxIntroduction: Palliative chemotherapy is the principal treatment of patients with advanced soft tissue sarcomas (STS); however prognosis is limited (median overall survival 12-19 months). In this setting, patient values and priorities are central to personalised treatment decisions. Patients and methods: The prospective HOLISTIC study was conducted in the UK and the Netherlands assessing healthrelated quality of life in STS patients receiving palliative chemotherapy. Participants completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Treatment decision-making in patients with soft tissue sarcoma is often complex; systemic treatment options often have significant side effects, and the benefits are often relatively modest. The mGPS is worth further evaluation in patients with advanced soft tissue sarcoma to help inform these decisions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment decision-making in patients with soft tissue sarcoma is often complex; systemic treatment options often have significant side effects, and the benefits are often relatively modest. The mGPS is worth further evaluation in patients with advanced soft tissue sarcoma to help inform these decisions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that the QoL of sarcoma patients appears to be stable. 2,[33][34][35][36][37][38] However, other research found more compromised levels of QoL. 39 Sarcoma patients experience lower QoL compared to the general population, 2,4,33,35,40 in different age groups, 41 even if other research detected poorer physical functioning but fewer symptoms such as fatigue and sleep disturbances in sarcoma patients than in the normative population.…”
Section: Quality Of Lifementioning
confidence: 95%
“…QoL is a well‐explored aspect of the experience of illness in sarcoma patients. Some studies show that the QoL of sarcoma patients appears to be stable 2,33–38 . However, other research found more compromised levels of QoL 39 …”
Section: Sarcoma Patientsmentioning
confidence: 99%
“…Health-related quality of life (HRQoL) is a multidimensional concept that includes the patient’s perception of the impact of the disease and its treatment on physical/biological, psychological and social functioning [ 10 ]. Better knowledge of HRQoL is essential to provide patient-centered care, as cancer patients consider HRQoL to be an important (treatment) outcome [ 9 , 11 ]. Moreover, cured patients and long-term survivors may have long-lasting problems which may be overlooked without a proper HRQoL assessment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%